2008
DOI: 10.4103/1477-3163.44372
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of EGFR and c-Met pathways, cross-talk and inhibition, in non-small cell lung cancer

Abstract: Backgroundc-Met and EGFR receptors are widely expressed on cancer cells; they are implicated in the development and progression of cancer through a plethora of effects on cell cycle progression, apoptosis, motility and metastasis and are potential targets for combination therapy. EGFR receptor tyrosine kinases are currently being targeted in a number of malignancies.MethodsApoptosis was studied by FACS analysis using propidium iodide. EGF and HGF signaling intermediates were studied by western blotting. Cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
149
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(156 citation statements)
references
References 36 publications
7
149
0
Order By: Relevance
“…These preclinical studies suggested that the combination of inhibitors for MET and EGFR RTKs could potentially produce synergistic antitumor effects (24). Indeed, a synergistic effect on inhibition of cell proliferation and apoptosis was seen when a novel first-generation MET inhibitor, SU11274, was combined with EGFR inhibitors such as AG1478 or gefitinib (24). The synergism and cross-talk of EGFR and MET pathways in NSCLC, and the potential of simultaneous inhibition, were thus recognized in these studies.…”
Section: Hfg/met In Lung Cancermentioning
confidence: 88%
See 2 more Smart Citations
“…These preclinical studies suggested that the combination of inhibitors for MET and EGFR RTKs could potentially produce synergistic antitumor effects (24). Indeed, a synergistic effect on inhibition of cell proliferation and apoptosis was seen when a novel first-generation MET inhibitor, SU11274, was combined with EGFR inhibitors such as AG1478 or gefitinib (24). The synergism and cross-talk of EGFR and MET pathways in NSCLC, and the potential of simultaneous inhibition, were thus recognized in these studies.…”
Section: Hfg/met In Lung Cancermentioning
confidence: 88%
“…Indeed, synergistic effects of epidermal growth factor (EGF) and HGF on proliferation, and additive effects on motility, were noted in preclinical studies in NSCLC cells. For example, increased membrane ruffling to form a motile cell surface was observed when cells were stimulated with HGF and EGF independently, and when these growth factors were combined, an additive effect was observed (24). These preclinical studies suggested that the combination of inhibitors for MET and EGFR RTKs could potentially produce synergistic antitumor effects (24).…”
Section: Hfg/met In Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The activated receptors such as VEGFR, EGFR, and c-Met play very important roles in the proliferation of cancer cells including lung cancer cells (Colon et al 2009;Kim et al 2008;Morelli et al 2006;Naumov et al 2009;Puri and Salgia 2008). In order to clarify the bufalin-targeted receptors in A549 cells, we studied the effects of bufalin on the related receptor phosphorylation and expressions in A549 cells.…”
Section: Bufalin Reduces the Receptor Phosphorylation And/or Protein mentioning
confidence: 99%
“…Suppression of the activated EGFR and ERK1/2 and p38 MAPKs as well as Akt signaling pathways led to inhibition of the proliferation of A549 cells (Baldys et al 2007;Nguyen et al 2004;Recchia et al 2009;Su et al 2010). There has been the cross-talk in EGFR and c-Met pathways in A549 cells which is related to the A549 cell proliferation (Puri and Salgia 2008). Suppression of EGFR, VEGFR, and c-Met led to inhibition of A549 cell proliferation in vitro and in vivo (Colon et al 2009;Kim et al 2008;Morelli et al 2006;Naumov et al 2009).…”
Section: Bufalin Reduces the Receptor Phosphorylation And/or Protein mentioning
confidence: 99%